VERIFICATION THE INCIDENCE OF COMPLAINTS OF TEACHERS IN MUSCULOSKELETAL IN STATE EDUCATION OF THE CITY OF PALMAS-PR (Fiep Bulletin - online, 2013)
Like any other worker teachers also suffer from occupational diseases arising from factors such as mechanical repetitive tasks or those generated by the inadequacy of the desktop and even the sensation of low valuation professional. During the months of October to December 2008 we conducted a cross-sectional study with 70 teachers investigative 5 schools in the urban area of the State Schools of the city of Palmas - PR for the investigation of complaints that may lead to the diagnosis of CTD / WMSD. To obtain the data we used the Nordic Questionnaire for Analysis of Musculoskeletal Symptoms of Commitment proposed by Kuorinka et al. (1987). A survey of teachers found out that the teachers interviewed N = 70, N = 64 (91.4%) reported having already made ??some musculoskeletal discomfort and only N = 6 (8.6%) reported no complaints, the number complaints was estimated at 4.36 for each teacher, that number considered significant. The region of greatest complaint was the shoulder region, N = 39 (61%), this region was also raised that the increased demand for medical services, the region with the highest rate of chronic pain was the neck N = (42, 2%); regarding absences from work during the last year, arising from complaints investigated, the vast majority did not lead to expulsion. It is concluded that the number of reported complaints this study shows a significant rate.
Keywords: health; teachers; musculoskeletal complaints